2016
DOI: 10.3384/ecp10305
|View full text |Cite
|
Sign up to set email alerts
|

The Sound Challenge to Visualization Design Research

Abstract: This paper is an introduction to the emotional qualities of sound and music, and we suggest that the visual and the aural modalities should be combined in the design of visualizations involving emotional expressions. We therefore propose that visualization design should incorporate sonic interaction design drawing on musicology, cognitive neuroscience of music, and psychology of music, and identify what we see as key research challenges for such an approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It would be interesting to further explore the interplay between colors, musical elements, and the perception of emotions in a future version of Photone. Musical sounds are well adapted, at least on a more general level, to conveying meaning and emotions (see for example discussions in [13,14]). Not only music affects emotions but also colors are associated with emotions [15], and there are correlations between the emotional associations of music and of colors [16].…”
Section: Future Design and Research Ideasmentioning
confidence: 99%
“…It would be interesting to further explore the interplay between colors, musical elements, and the perception of emotions in a future version of Photone. Musical sounds are well adapted, at least on a more general level, to conveying meaning and emotions (see for example discussions in [13,14]). Not only music affects emotions but also colors are associated with emotions [15], and there are correlations between the emotional associations of music and of colors [16].…”
Section: Future Design and Research Ideasmentioning
confidence: 99%
“…Recent examples of this trend include "data cuisine" [12], "data pottery" [13] and "data sculpture" [14]. Among this emerging trans-disciplinary practice, data visualisation experts are timidly starting to recognise the potentialities of sound and music as an effective way of communicating emotional connotations of information, through qualities such as tempo, volume, or timbre [15].…”
Section: Humanising Datamentioning
confidence: 99%
“…In the history of sonification, the Geiger-counter is possibly the most quoted [22] and the most successful example of using sound to monitor and alert users, and the one stuck into the collective memory. But more recently multimodal design research has shown a renewed interest in leveraging sound specificities, drawn mainly from psychology and psychoacoustics, cognitive sciences and neurosciences [15], to design more efficient user experiences in order to increase the information bandwidth and avoid information overload in Virtual Reality (VR) highly complex environments [17]. Maybe surprisingly, in these contexts not only functionality and efficiency but also the aesthetic of sound appears as an increasingly important characteristic to make auditory feedbacks more relevant and easier to interpret [37].…”
Section: Sonification In a Multi-modal Contextmentioning
confidence: 99%
“…The ability of sound to both be part of the peripheral awareness and to be experienced intentionally and attentionally (that is, focally) is something that makes sound different from visual stimuli. The auditory system has a very high resolution in terms of frequency discrimination as well as temporal resolution and perception of loudness levels, and musical sounds are well adapted to convey a multitude of information to listeners, quickly and intuitively (Tsuchiya, 2015), communicating meaning, information, and emotions (see for example discussions in Rönnberg, 2016, andTsuchiya, 2015) on a general level. This makes sound suitable for creating sonic moods, providing peripheral information, conveying general information about states in dynamic processes, and more.…”
Section: Introductionmentioning
confidence: 99%